Analysis of Drug Compliance in Pulmonary TB Patients Reviewing from Attitude, Motivation and Family Support - Setyo Susilo; Yuly Peristiowati (Jurnal Keperawatan, 2023)
Pulmonary TB disease or known as TB is actually a curable disease, but many patients stop treatment prematurely. The purpose of this study is to analyzethe influence of attitude, motivation and family support on medication adherence in pulmonary TB patients in the work area of the Benjeng Health Center, Gresik Regency. The design of this research is an observational quantitative research with a cross sectional approach with the focus of the research being directed at analyzingthe influence of attitude, motivation and family support on medication adherence in pulmonary TB patients in the work area of the Benjeng Health Center, Gresik Regency. The total population of 143 respondents and a sample of 105 respondents were taken using the Simple Random Sampling technique. The findings showed that almost half of the respondents have a moderate attitude category as many as 46 respondents (43.81%). Almost half of the respondents have a moderate category of motivation as many as 45 respondents (42.86%). Almost half of the respondentshave adequate family support category as many as 48 respondents (45.71%). Most respondents 60 respondents (57.1%). Based on the results of Multiple Linear Regression analysis shows that with a p-value of 0.000 <0.05 then H1 is accepted so it can be concluded that simultaneously there isinfluenceattitude, motivation and family supporttomedication adherence in pulmonary TB patients in the work area of ​​the Benjeng Public Health Center, Gresik Regency with an effect of 82.7%.